KERAGAAN AGROINDUSTRI KERUPUK BAWANG WINDA PUTRI DI KECAMATAN TANJUNG SENANG KOTA BANDAR LAMPUNG - Ayu Nirmala Lutfie Syarief; Dyah Aring Hepiana Lestari; Eka Kasymir (Lampung University, 2019)
The purposes of this research are to analyze procurement process of raw materials that correspond to six right on (time, place, quality, quantity, type, and price), added value and income of onion cracker processing activities, marketing mix, distribution channels, marketing margins, and the role of support services. This research was a case study method at onion cracker agroindustry in Tanjung Senang Sub-district of Bandar Lampung City. The data collection was conducted in January - February 2018 and was analyzed by qualitative and quantitative descriptive analysis. The results showed that the procurement of raw materials had not fulfilled price component. The production performance of the agroindustry was not good because it had not fulfilled the flexibility component. The agroindustry revenue was considered good because the value of R/C ratio was > 1 and given added value was positive. The marketing strategy of the agroindustry has used the 4P marketing mix component, in which product and price were well, while the place and promotion component have not been used optimally. The marketing chains consisted of two channels. The provided support services of this agroindustry were bank, information and communication technology, transportation, and marketKey words: agroindustry, onion cracker, performance